Analisis Sifat-sifat Optoelektronik Lapisan Tipis Silikon Amorf terhidrogenasi yang ditumbuhkan dengan Teknik VHF-PECVD pada Variasi Daya RF - Ida Usman; Amiruddin Supu; Mursal Mursal; Sukirno Sukirno; Toto Winata; Mohamad Barmawi (Institut Teknologi Bandung, 2005)
The hydrogenated amorphous silicon (a-Si:H) thin films have been deposited using VHF-PECVD technique. The deposition process was done by varied the rf power from 6 to 12.5 watts with 300 mTorr of chamber pressure and from 20 to 70 watts with 100 mTorr of chamber pressure. The highest deposition rate of 2.99 Ã /sec and the highest photoconductivity of 1.13 x 10-4 S/cm were obtained from 8 watts of rf power when the rf power was varied from 6 to 12.5 watts. Then, the highest deposition rate of 9.57 Ã /sec was obtained from 40 watts of rf power and the highest photoconductivity of 1.54 x 10-2 S/cm was obtained from 20 watts of rf power when the rf power was varied from 20 to 70 watts. Based on the analysis of characterization results, the degradation of a-Si:H film conductivity was caused by the formation of defect states such as band-tail defect and bandgap defect.